HYGIENIC HABITS AND ITS RELATION TO MICROBIAL LOAD ON SMOKED HERRINGS (CLUPEA HARENGUS) IN SABON GARI MARKET, KADUNA STATE, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2025)
Smoked fish particularly Clupea harengus (herring) is an important and relatively cheap animal protein component in the diet of Nigerians making its consumption and trade a common nutritional and commercial practice. However, the safety of these products is increasingly under scrutiny due to microbial contamination risks associated with poor hygienic practices. This study evaluates the relationship between hygienic habits of vendors and microbial load on smoked herrings sold in Sabon Gari Market, Kaduna State between late March and early May, 2023. A total of 60 C. harengus samples were obtained and analysed using Standard microbiological procedures (serial dilution, pour plate method, and biochemical identification tests). Three different species of microorganisms comprising Escherichia coli, Salmonella spp and Staphylococcus aureus were isolated and Total Viable Count determined (TVC). Descriptive statistics revealed alarmingly high microbial loads, with E. coli (28 CFU/g) and S. aureus (11.57 CFU/g) levels exceeding acceptable thresholds. Although correlation analyses showed a negative association between hygiene scores and microbial levels, ANOVA results indicated no statistically significant differences (p< 0.05) in microbial load across hygiene categories. The findings underscore the need for enhanced hygiene training, market infrastructure improvement, and stricter food safety enforcement to protect public health.
Keywords: Smoked fish; Clupea harengus; Hygiene practices; Microbial contamination; Food safety